2019
DOI: 10.17219/acem/94155
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brain and body imaging in the MR-compatible incubator

Abstract: Background. The use of a specialized MR-compatible incubator (INC) is very poorly described in the literature and only with regard to brain imaging. Objectives. To present our own experience with brain and body magnetic resonance imaging (MRI) in the INC in a large cohort of neonates. Material and methods. A total of 555 examinations were performed in 530 newborns with the use of a 1.5T system and Nomag IC 1.5 incubator, equipped with head and body coils. Results. More than half of neonates (54%) were prematur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Due to acquiring our MRI compatible incubator during the study course, we could show as a secondary finding that our completion rate was improved, compared to when using the bassinet. This is in keeping with neonatal neuroimaging studies using an MRI-compatible incubator, which have shown shorter image acquisition time and improved image quality, potentially explained by enhanced noise cancellation [33][34][35] as well as externally controlled consistent ambient temperature for the neonate in the incubator.…”
Section: Secondary Findingssupporting
confidence: 80%
“…Due to acquiring our MRI compatible incubator during the study course, we could show as a secondary finding that our completion rate was improved, compared to when using the bassinet. This is in keeping with neonatal neuroimaging studies using an MRI-compatible incubator, which have shown shorter image acquisition time and improved image quality, potentially explained by enhanced noise cancellation [33][34][35] as well as externally controlled consistent ambient temperature for the neonate in the incubator.…”
Section: Secondary Findingssupporting
confidence: 80%
“…ROS-mediated molecular networks, like PI3K-Akt-mTOR, TLR-4, IGF, MAPK, and AMPK, rely upon a several distinct mechanisms including catalase or caspase activation of autophagy-related genes, and disturbances in the mitochondrial electron transport chain [55]. In any case, oxidative stress mediated autophagy in HIE stays dubious, and whether there is a beneficial or detrimental role of autophagy relies upon whether intracellular stresses have been resolved [56].…”
Section: Oxidative Stress Mediated Autophagy In Hiementioning
confidence: 99%
“…Neuroimaging is significant in determining the etiology of neonatal encephalopathy, guiding clinical decision making, giving prognosis after hypoxic ischaemic injury and informing risk management and medico-legal proceedings [56].…”
Section: Clinical Guidelines 1 Imaging the Encephalopthic Infantmentioning
confidence: 99%
See 2 more Smart Citations